Inconsistency of The Principle of Horizontal Separation in Law Number 4 of 1996 Concerning Mortgage Rights - Ni Luh Ari Andini Adnyana; I Wayan Novy Purwanto (NOTARIIL Jurnal Kenotariatan, 2025)
The objective of this study is to analyze the inconsistency in the application of the horizontal separation principle within Law No. 4 of 1996 on Mortgage Rights over Land and Objects Related to Land, as well as its legal consequences. This research employs a normative legal research method with a statute approach, focusing on the analysis of legal norms, principles, and regulations. The data collection technique involves a literature review of journals, books, and relevant legal provisions. The findings indicate that although the horizontal separation principle is incorporated into the Indonesian agrarian legal system under the Basic Agrarian Law (UUPA), inconsistencies arise from the misalignment between UUPA and the Mortgage Rights Law (UUHT). These inconsistencies result in uncertainties regarding collateral objects, insufficient protection for building owners who do not hold ownership over the land, and potential obstacles in the execution of creditor’s rights. It is necessary to harmonize the two legal frameworks to establish clearer and more reliable legal certainty.